An easy way to increase confidence in beta-amyloid PET evaluation - Belohlavek, Otakar; Jaruskova, Monika (Nuclear medicine review. Central & Eastern Europe, 2017)
BACKGROUND: In patients with brain atrophy, it is not easy to distinguish pathologic uptake of flutemetamol (FMM) in the gray matter from nonspecific, physiologic uptake in the white matter. In this paper we suggest an easy image processing method. MATERIAL AND METHODS: The proof-of-concept study involved three patients with mild cognitive impairment and different graphical findings at FMM-PET. Two-phase FMM-PET was acquired; the early phase represented the perfusion of gray matter, while the late phase depicted the white matter and beta-amyloid load in the gray matter. The border of the gray matter was easily extracted from the early-phase images using thresholding and the isocontour "Edges" color table. The late phase was registered with the edge images of the early phase and displayed using alpha-blending. RESULTS: Early- and late-phase image fusion displayed with appropriate color tables is presented in three different cases to illustrate the added value of the suggested approach. CONCLUSIONS: Composite late-phase images with enhanced gray matter borders strongly facilitate assessment of beta-amyloid presence in the gray matter. This is especially helpful in patients with brain atrophy.
Keywords: positron-emission tomography; flutemetamol; dementia; atrophy; amyloid; brain